2020
DOI: 10.16910/jemr.13.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Fixation duration and the learning process: an eye tracking study with subtitled videos

Abstract: Learning is a complex phenomenon and education researchers are increasingly focussing on processes that go into it. Eye tracking has become an important tool in such research. In this paper, we focus on one of the most commonly used metrics in eye tracking, namely, fixation duration. Fixation duration has been used to study cognition and attention. However, fixation duration distributions are characteristically non-normal and heavily skewed to the right. Therefore, the use of a single average value, such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 40 publications
2
18
1
Order By: Relevance
“…Moreover, eye movement analyses revealed that, compared to low-VSA players, high-VSA players exhibited longer eye fixations followed by shorter and slower saccades which represent focal processing and conscious perception of the presentation’s key elements. By contrast, low-VSA players had ambient spatial processing that did not enable a conscious identification of the presentation’s elements (Eisenberg & Zacks, 2016; Negi & Mitra, 2020). Second, a significant interaction between VSA and visual realism indicated that, in addition to achieving higher performance than low-VSA players, high-VSA players benefited more from reduced visual realism to memorize soccer tactics.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, eye movement analyses revealed that, compared to low-VSA players, high-VSA players exhibited longer eye fixations followed by shorter and slower saccades which represent focal processing and conscious perception of the presentation’s key elements. By contrast, low-VSA players had ambient spatial processing that did not enable a conscious identification of the presentation’s elements (Eisenberg & Zacks, 2016; Negi & Mitra, 2020). Second, a significant interaction between VSA and visual realism indicated that, in addition to achieving higher performance than low-VSA players, high-VSA players benefited more from reduced visual realism to memorize soccer tactics.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, a well-designed presentation should direct the user’s scanning to the desired targets with few interim fixations, which should result in quicker and larger saccades. However, added visual realism induced shorter and slower saccades, which indicates difficulties in extracting visual elements, preceded by longer fixations that indicate a greater processing demand (Negi & Mitra, 2020; Sáiz-Manzanares et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Gaze is the dwell of the human eye while observing a target, and most of the information acquired by the user’s eye is processed and extracted while gazing. The average duration duration reflects the processing time of the target information in the region [ 50 ]. An interface with complex information takes longer for the user to process and extract, and the duration of the duration becomes longer.…”
Section: Resultsmentioning
confidence: 99%
“…In the eye tracking literature, longer fixation durations correspond to engaging more with the object or increased cognitive process [30]. Fixation durations are mainly related to cognition and attention; however, it is argued that they are affected by the procedures that lead to learning and it is reported that fixation durations can be used to understand learning processes as well [43]. For instance, [15] has studied fixation patterns during learning in simulation-and microcomputer-based laboratory and found that simulation group had longer fixation duration, which means more attention and deeper cognitive processing.…”
Section: Measurementsmentioning
confidence: 99%